Influence of Starting-Block Angle on the grab start in competitive swimming - Stevenson, J. R.; Morehouse, C. A. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The purpose of this study was to determine, through the use of cinematography and a strain-gauged starting block, the effects of starting-block angles of 0°, 10°, 20°, and 30° above the horizontal on a 22.86-m (25-yard} swimming performance using the grab start. The differences in the grab-start performances from the four block angles were analyzed with respect to 15 selected biomechanical factors, which included the angles of projection at takeoff and incidence at water entry, takeoff and entry velocities, horizontal distance of projection, vertical hand forces on the front edge of the starting block, and time data for various phases of the start.